Suggestion for Modify of the School Educational Program at the Secondary Vocational School of Electrical Engineering - BENEŠOVÁ, HANA; MACH, PETR (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
This article deals with the suggestion for modify the school education program at the Secondary Vocational School of Electrical Engineering, Pilsen, specifically by adding a chapter on thin film photovoltaic to the curriculum of the subject Use of Electric. The photovoltaic is increasingly considered to be one of the most important technologies of the 21st century. For this reason it is necessary to provide the students some information on this issue and to expand their competences.